2015
DOI: 10.1158/1078-0432.ccr-14-2793
|View full text |Cite
|
Sign up to set email alerts
|

Serum miR-21, miR-29a, and miR-125b Are Promising Biomarkers for the Early Detection of Colorectal Neoplasia

Abstract: Purpose Circulating microRNAs (miRNAs) are emerging as promising diagnostic biomarkers for colorectal cancer (CRC), but their usefulness for detecting early colorectal neoplasms (CRNs) remains unclear. This study aimed to identify serum miRNA biomarkers for the identification of patients with early CRNs. Experimental Design A cohort of 237 serum samples from 160 patients with early CRNs (148 precancerous lesions and 12 cancers) and 77 healthy subjects was analyzed in a three-step approach that included: a co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
97
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(104 citation statements)
references
References 32 publications
6
97
0
Order By: Relevance
“…Recently, several papers have reported the usefulness of plasma/serum miR-21 levels as a biomarker for diagnosis in CRC patients [23,24,25,26,27,28]. However, the clinical significance of plasma/serum miRNA as a biomarker for diagnosis is still controversial, and some papers have indicated that serological miR-21 does not have any impact on diagnosis in CRC patients [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several papers have reported the usefulness of plasma/serum miR-21 levels as a biomarker for diagnosis in CRC patients [23,24,25,26,27,28]. However, the clinical significance of plasma/serum miRNA as a biomarker for diagnosis is still controversial, and some papers have indicated that serological miR-21 does not have any impact on diagnosis in CRC patients [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…A few recent studies have revealed the diagnostic role of circulating miRNAs in CRC [13, 14, 18]. Unfortunately, to date, independent studies have failed to develop clinically actionable miRNA biomarkers for a variety of reasons including population and sample diversity, especially the discovery and validation methodologies used in these reports.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that miRNAs can be stably detected in serum or plasma and have the potential to be new biomarkers for early diagnosis of various types of cancers [912]. Additionally, several studies have revealed that some miRNAs are able to discriminate CRC patients from healthy controls and serve as serum biomarkers for CRC screening with high accuracy [13, 14]. However, these results lack consistencies because of different research methods and tested populations between laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…In colorectal cancer (CRC), the expression of miR-125b was downregulated (32), while in patients with early colorectal neoplasia (including precancerous lesions and early CRCs) the expression of serum miR-125b was also upregulated compared with healthy controls. Therefore, miR-125b may be used as biomarker for early detection of colorectal neoplasia (33). Thus, the expression of miR-125b in different stages of tumors varies, indicating that the role of miR-125b is constantly changing during the tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%